INTEGRATING HOUSING ENVIRONMENTAL FACTORS INTO THE SEIR MODEL FOR PULMONARY TUBERCULOSIS TRANSMISSION: A CASE STUDY IN BANJAR, INDONESIA - Yuni Yulida; Eko Suhartono; Dewi Anggraini; Syamsul Arifin (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
Pulmonary Tuberculosis (TB) remains one of the serious public health issues in Indonesia, including in Banjar Regency. The transmission of TB is not only influenced by biological and behavioral factors but also highly depends on the characteristics of the living environment. This study aims to analyze the influence of physical environmental factors of housing on the incidence of pulmonary TB, and to integrate the analysis results into a modified SEIR model. The research was conducted using a cross-sectional observational approach involving 73 respondents from the working areas of Puskesmas Martapura 1 and Martapura 2. Data were collected through direct observation and interviews, and analyzed using binary logistic regression to identify significant variables. The significant variables were subsequently integrated into the transmission rate parameters in the SEIR model. The results show that ventilation area and room temperature have a significant impact on the incidence of pulmonary TB. Empirical findings show that the probability of pulmonary TB incidence is highest (86.68%) when both ventilation and temperature are below standard, and lowest (26.23%) when both meet the standards. Partial compliance still results in a high probability of incidence (around 60%). The SEIR model simulation with environmental scenarios shows that living conditions that do not meet ventilation area and temperature standards result in more aggressive TB transmission. Conversely, living conditions that meet both standards significantly reduce the number of infected individuals and increase the recovery rate. This research emphasizes the importance of environment-based interventions in a comprehensive TB control strategy.